"A study in grey": a critical reflection on scientific (mis)behaviors in quantitative inquiries. (3rd April 2021) - Derdowski, Lukasz
ABSTRACT: Application of quantitative techniques in the study of tourism phenomena has gained momentum in the last two decades. Various quantitative methods allow researchers to investigate problems encompassing, for instance, tourists' behaviors, destinations efficiency, or tourism demand forecasting. However, statistical apparatus in the hands of a professional can either reveal a great deal about the world or conversely, deceive thousands of people. Past research touching upon the subject of scientific misbehaviors focused primarily on answering questions of who?, when? or how often?, leaving the matter of how specifically? rather uninvestigated. In the current paper, a grey area between quantitative data modification and falsification is discussed with the intention to build greater awareness among undergraduate students about potential pitfalls related to the execution of quantitative inquiries. To increase transparency and credibility of future scientific endeavors, practical recommendations are proposed on how to work responsibly within the confines of quantitative tourism research.